SEMANTIC CHANGE AND ITS IMPLICATIONS IN MODERN ENGLISH - Rika Budiarti; Bernieke Anggita Ristia Damanik (JOURNAL SAINS STUDENT RESEARCH, 2025)
This mini research examines how meanings of words in English change over time and how these changes affect modern language use. Semantic change includes several processes, such as the expansion or restriction of meaning, improvement or worsening of connotation, and shifts in meaning. As stated by Ullmann (1962), changes in word meanings naturally occur in all living languages as a reflection of cultural and social evolution. By analyzing current examples, this study shows how such changes influence how people communicate, how English is taught, and how vocabulary is understood. Recognizing semantic change is important for both native speakers and learners to keep up with the evolving use of language.